Patisiran in ATTRv amyloidosis with polyneuropathy: “PatisiranItaly” multicenter observational study - Di Stefano, Vincenzo; Guaraldi, Pietro; Romano, Angela; Antonini, Giovanni; Barilaro, Alessandro; Briani, Chiara; Burattini, Marco; Cani, Ilaria; Carlini, Giulia; Ceccanti, Marco; Cianci, Vittoria; Cortelli, Pietro; et al. (Journal of neurology, 2025)
Background Hereditary amyloid transthyretin amyloidosis with polyneuropathy (ATTRv-PN) is a rare, inherited, multisystemic, progressive adult-onset disease, affecting sensorimotor nerves, and various organs. It is caused by mutations in the TTR gene, leading to misfolded monomers that aggregate, forming amyloid fibrils. Patisiran is a small, double-stranded interfering RNA encapsulated in a lipid nanoparticle, designed to enter hepatocytes and selectively target TTR mRNA to reduce both variant TTR and wild-type TTR (wt). This study presents a multicenter, real-life experience of patisiran’s effectiveness and safety in ATTRv-PN. Methods We enrolled genetically confirmed ATTRv-PN patients from 29 specialized Italian centers. All subjects underwent neurological assessments, including familial amyloid polyneuropathy (FAP) staging, the Neuropathy Impairment Score (NIS), quality-of-life assessment using the Norfolk Quality of Life-Diabetic Neuropathy (Norfolk QOL-DN) questionnaire, and the Compound Autonomic Dysfunction Test (CADT). Additional assessments included baseline and follow-up measures of serum NT-proBNP and interventricular septal thickness. Results A total of 181 ATTRv patients (69% male) were enrolled. Neurological onset was reported in 60.2% of cases. At baseline, 83.4% of patients exhibited multisystemic involvement, while only 16.6% presented isolated polyneuropathy. For approximately 70% of patients, patisiran was the first treatment; the remainder transitioned from tafamidis or inotersen. Following treatment, most patients demonstrated stabilization of neuropathy progression, regardless of baseline disease severity or genotype. The treatment was well-tolerated, with 90% of patients reporting no adverse events. Conclusion Patisiran can be considered a valid therapeutic option for the management of patients with ATTRv amyloidosis. Considering its mechanism of action, similar outcomes could also be expected with the wider utilization of newly approved gene silencers for ATTRv therapy, such as vutrisiran.